Preparation and characterization of intelligent starch/PVA films for simultaneous colorimetric indication and antimicrobial activity for food packaging applications. (10th February 2017) - Liu, Bin; Xu, Han; Zhao, Huiying; Liu, Wei; Zhao, Liyun; Li, Yuan
Highlights: Smart starch/PVA film having color indication and antimicrobial properties was developed. The real-time pH variation of foods can be monitored by the color change of the film. The film can effectively inhibit pathogen growth such as Staphylococcus aureus . Abstract: We have developed an intelligent starch/poly-vinyl alcohol (PVA) film that is capable of monitoring pH changes and inhibiting undesired microbial growth in foods. Starch and PVA polymers in the film were doubly cross-linked by sodium trimetaphosphate and boric acid to improve their water-resistance and mechanical strength. Anthocyanins (ANT) and limonene (LIM) were used to achieve simultaneous colorimetric indication and antimicrobial activity. Firstly, the characterization of surface morphology using SEM confirmed that the starch-PVA-ANT-LIM film possessed a smooth surface. Secondly, the results of the mechanical strength test showed that starch-PVA-ANT-LIM possesses the highest mechanical strength. Additionally, there was a distinguishable change of colors as the film was immersed in solutions of pH ranging from 1.0 to 14.0. Moreover, the film showed excellent antimicrobial activity for three typical undesired microorganisms in foods, Bacillus subtilis, Aspergillus niger, and Staphylococcus aureus . Finally, the film exhibited good color indication and antimicrobial activity on pasteurized milk. The results suggest that the intelligent film reported here shows good capability for both alerting and inhibiting food spoilage.